Maternal near miss morbidity in Colombia: variables related to opportune access to health care related to the number of inclusion criteria (2014)
Background. In Colombia, maternal near miss morbidity is monitored in the health surveillance system. The National Health Institute included a special report on cases that met three or more World Health Organization criteria according to the World Health Organization criteria.Objective. To estimate the relationship between variables related to opportune access to health care services in Colombia during 2013 depending on inclusion criteria –three or more– for maternal near miss morbidity.Materials and methods. A cross-sectional analysis of the national registry of obligatory notification on maternal near miss morbidity was performed. Cases with three or more criteria were compared with those with one or two according to some variables related to the timely access of health care services.Results. A total of 8 434 maternal near miss morbidity cases were reported, women were aged between 12 and 51 years old (M=26.4, SD=7.5). 961 (11.4%) lived in remote rural areas; 4 537 (53.8%) were uninsured under the health system, or they were affiliated to either the subsidized or special health care regime; 845 (10.0%) belonged to an ethnic minority; 3 696 (44.4%) were referred to a more complex service; 4 097 (49.2%) were admitted to the intensive care unit; and 3 975 (47.1%) met three or more of the inclusion criteria for maternal near miss morbidity. They were combined to meet three or more of the case inclusion criteria: intensive care unit admission (OR=5.58; IC95% 5.06-6.15); being uninsured or affiliated to the subsidized or special regime (OR=1.57; IC95% 1.42-1.74); and referral to a more complex service (OR=1.18; IC95% 1.07-1.31).Conclusions. In Colombia, the timely access of health care services is related to maternal near miss morbidity with three or more inclusion criteria.